(untitled) (Archives of Clinical Psychiatry, 2007)
BACKGROUND: The early detection and intervention in schizophrenia are new areas of research in great expansion. OBJECTIVE: To review the literature about early detection and intervention in schizophrenia. METHOD: Literature was studied by means of PubMed, manuals and bibliographic references and used the search terms: "high risk", "early intervention", "early detection", "schizophrenia", "early psychosis". RESULTS: Using paradigms of selective and indicated prevention of other fields of Medicine, it studies the initial manifestations of schizophrenia, even before clear psychotic symptoms are manifest. CONCLUSION: Early detection and intervention of individuals at risk to develop psychosis aim to reduce the duration of untreated psychosis, to improve the course and outcome of the disease, and maybe prevent the manifestation of schizophrenia in predisposed individuals.